Isometric quadriceps exercises for patients with knee osteoarthritis: A randomized controlled trial comparing knee joint position flexion versus extension - Şengül, Alaattin; Yavuzer, Melek Güneş; Keleş, Özal; Tunalı, Ayşe Nur; Tuncer, Deniz (Hindawi Limited, 2022)
Objective. To compare the effect of quadriceps isometric exercises performed in two different positions in addition to the combined physical therapy program on pain, stiffness, and physical function in patients with knee osteoarthritis (OA). Methods. A total of 30 patients with OA (age range 45 to 70 years) who were admitted to Istanbul Private Ekotom Medical Center, Department of Physical Medicine and Rehabilitation Outpatient Clinic, were included. The patients were randomly divided into two groups according to the type of performing the quadriceps isometric exercises as group 1 (performing in knee extension, n=14) and group 2 (performing in knee flexion, n=15). All patients also received a combined physical therapy program. Exercise protocols were applied six days a week for four weeks. The pain was evaluated using a 10 cm visual analog scale for pain (VAS) in rest and activity; pain, joint stiffness, and physical function were assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Results. A significant difference was found in the VAS and WOMAC scores of both groups in group comparisons (p < 0.05). When the groups were compared in terms of change values, a significant difference was found in the WOMAC stiffness score in favor of group I (p < 0.05). Discussion. It is possible to obtain positive results with quadriceps isometric exercises to reduce pain and joint stiffness and increase physical function in patients with knee OA. However, exercises performed in knee extension were found to be more effective in reducing joint stiffness.
Keywords: Rheumatoid-Arthritis; Older-Adults; Muscle; Strength